Analysis of internal astigmatism and higher order aberrations in eyes implanted with a new diffractive multifocal toric intraocular lens - Mojzis, Peter; Piñero, David P; Ctvrteckova, Vera; Rydlova, Iva (Graefe's archive for clinical and experimental ophthalmology, 2013)
BACKGROUND: To evaluate the intraocular lens (IOL) position by analyzing the postoperative axis of internal astigmatism as well as the higher-order aberration (HOA) profile after cataract surgery following the implantation of a diffractive multifocal toric IOL METHODS: Prospective study including 51 eyes with corneal astigmatism of 1.25D or higher of 29 patients with ages ranging between 20 and 61 years old. All cases underwent uneventful cataract surgery with implantation of the AT LISA 909 M toric IOL (Zeiss). Visual, refractive and corneal topograpy changes were evaluated during a 12-month follow-up. In addition, the axis of internal astigmatism as well as ocular, corneal, and internal HOA (5-mm pupil) were evaluated postoperatively by means of an integrated aberrometer (OPD Scan II, Nidek). RESULTS: A significant improvement in uncorrected distance and near visual acuities (p < 0.01) was found, which was consistent with a significant correction of manifest astigmatism (p < 0.01). No significant changes were observed in corneal astigmatism (p = 0.32). With regard to IOL alignment, the difference between the axes of postoperative internal and preoperative corneal astigmatisms was close to perpendicularity (12 months, 87.16° ± 7.14), without significant changes during the first 6 months (p ≥ 0.46). Small but significant changes were detected afterwards (p = 0.01). Additionally, this angular difference correlated with the postoperative magnitude of manifest cylinder (r = 0.31, p = 0.03). Minimal contribution of intraocular optics to the global magnitude of HOA was observed. CONCLUSIONS: The diffractive multifocal toric IOL evaluated is able to provide a predictable astigmatic correction with apparent excellent levels of optical quality during the first year after implantation.
Keywords: Humans; refrakce oka; Prosthesis Design; implantace nitrooční čočky; Astigmatism; astigmatismus; protézy - design; lidé; prospektivní studie; fakoemulzifikace; Corneal Topography; Phacoemulsification; pseudofakie; Prospective Studies; mladý dospělý; Refraction, Ocular; Female; Pseudophakia; lidé středního věku; Lenses, Intraocular; Aberrometry; Male; rohovkové aberace; nitrooční čočky; Lens Implantation, Intraocular; Corneal Wavefront Aberration; Adult; rohovková topografie; dospělí; aberometrie; Visual Acuity; zraková ostrost; Middle Aged; ženské pohlaví; mužské pohlaví; Young Adult